The effect of the modeling approach to enhance knowledge and skill of lactation management among primipara’s mother - Oktalesmana, Lina; Munir, Zainal; Nursiam, Wiwin (Universitas Aisyah Pringsewu, 2019)
A modeling approach to lactation management is a learning effort undertaken by mothers, fathers and families to support the success of breastfeeding by watching and paying attention to other people's behavior and then copying it. The purpose of this research was to analyze the knowledge and skills of primiparous mothers about lactation management before and after the modeling approach. This research method uses pre-experiment with one-group pre-post test design. The research population was all primiparous mothers whose babies were treated in level 2 perinatology, which were taken as accidental sampling involving 26 primiparous mothers. The method used in health education (penkes) is the Modeling approach with pantom tools, modules, and containers or bottles that have a lid. The modeling approach consists of four processes, namely Attention, Retention, Reproduction motori (reproduction), and motivation (motivation). The results showed that there was a significant influence between the modeling approach to the knowledge and skills of primiparous mothers in the perinatology room of Bondowoso Hospital.Abstrak: Pendekatan modeling tentang manajemen laktasi merupakan suatu upaya pembelajaran yang dilakukan oleh ibu, ayah dan keluarga untuk menunjang keberhasilan menyusui dengan melihat dan memperhatikan perilaku orang lain kemudian mencontohnya. Tujuan penelitian ini adalah untuk menganalisa pengetahuan dan keterampilan ibu primipara tentang manajemen laktasi sebelum dan sesudah dilakukan pendekatan modeling. Metode penelitian ini menggunakan pre experiment dengan rancangan one-grup pre-post test design. Populasi penelitian ini adalah seluruh ibu primipara yang bayinya dirawat diruang perinatologi level 2, yang diambil secara asidental sampling dengan melibatkan 26 ibu primipara. Metode yang digunakan dalam pendidikan kesehatan (penkes) adalah pendekatan Modeling dengan alat bantu pantom, modul, dan wadah atau botol yang mempunyai tutup. Pendekatan modeling terdiri dari empat proses, yaitu Perhatian (attention), Pengendapan (retention), Reproduksi motori (reproduction), dan motivasi (motivation). Dari hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan antara pendekatan modelling terhadap Pengetahuan dan keterampilan ibu primipara di ruang perinatologi rumah sakit Bondowoso.